Adsorpsi Selektif Ion Cd2+ Menggunakan Silika Mesopori MCM-48-NH2 - Andi Yanti Puspita Sari; Muhammad Mulyadi Nahrun; Besse Illang Sari; Siti Khairunnur (Lembaga Pengembangan Kinerja Dosen, 2025)
The danger of cadmium contamination in water sources remains a crucial environmental issue due to its persistent nature and high toxicity level, which poses serious risks to human health and ecosystems. Cadmium is a non-biodegradable heavy metal that can accumulate in living organisms over time. The presence of these toxic Cd²⁺ ions is known to trigger damage to vital organs such as the liver and kidneys; therefore, reducing their concentration in aquatic environments is of paramount importance for environmental protection and public health safety. Among various treatment methods, adsorption is considered one of the most effective and economical techniques for removing heavy metal ions from contaminated water. In this study, the capability of mesoporous silica MCM-48-NH₂ as an adsorbent for Cd²⁺ ions was systematically evaluated. The adsorption performance was examined by investigating several important parameters, including contact time, solution acidity level (pH), and initial Cd²⁺ concentration. Furthermore, the adsorption mechanism and interaction between Cd²⁺ ions and the adsorbent surface were analyzed using Langmuir and Freundlich isotherm models. The results demonstrate that the adsorption process of Cd²⁺ ions onto MCM-48-NH₂ tends to follow the Langmuir isotherm model, indicating monolayer adsorption behavior, with a maximum adsorption capacity of 0.66 mmol g⁻¹.